A novel device for trace metal‐clean sampling of bottom water and suspended particles at the ocean's lower boundary: The Benthic Trace Profiler. (11th December 2021) - Plass, Anna; Retschko, Anna‐Kathrin; Türk, Matthias; Fischer, Tim; Scholz, Florian
Abstract: The benthic boundary layer plays a crucial role in the exchange of trace metals between surface sediments and the water column. So far it has been difficult to study dissolved–particulate interactions of trace metals in this highly reactive interface layer due to the lack of suitable sampling methods. We developed a new device, called Benthic Trace Profiler (BTP), which enables simultaneous sampling of near‐bottom water and suspended particles in high depth resolution within the first 3 m above the seafloor. The device was tested successfully in the Baltic Sea. The concentrations of several trace metals (Co, Ni, Cu, Zn, and Cd) in the collected bottom waters overlapped with concentrations in water column samples above collected with conventional methods. This observation indicates that the sampling device and method is trace metal clean. The trace metals Fe and Mn showed concentration gradients within the benthic boundary layer indicating an upward diffusive flux. This observation is consistent with a diffusive benthic flux of these trace metals across the sediment–water interface, which was independently verified using pore‐water profiles. Suspended particles can be used to study precipitation processes and to determine the carrier phases of trace metals. The BTP fulfilled all the intended requirements as it allowed a simultaneous, uncontaminating and oxygen‐free sampling of seawater and suspended particles to gather high‐resolution profiles of dissolved and particulate trace metal concentrations above the seafloor. The device closes the gap between water column and sediment sampling and helps researchers to better understand trace metal exchange processes across the ocean's lower boundary.